Penerapan Model Pembelajaran Discovery Learning Berbantuan Media Augmented Reality Terhadap Hasil Belajar - Aidiyah Fitri Zahro; Ati Sadiah; Edi Fitriani Afriza (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
The research was motivated by the problems that occur at SMAN 19 Bekasi City regarding learning outcomes, namely there are still students who have not been able to meet the Criteria for Achieving Learning Objectives (KKTP). The purpose of the study was to determine the application of the discovery learning model assisted by augmented reality media in improving student outcomes, especially economic subjects. The research method is quasi experiment with nonequivalent control group design. Data collection techniques, then data management techniques, and data analysis through tests in the form of multiple choice consisting of 30 questions. The research population was all class X students of SMAN 19 Bekasi City in the 2024/2025 academic year, totaling 213 students. Non-probability sampling technique purposive sampling type with a total sample of 70 students, consisting of 35 students from class X-E as the experimental class, and 35 students from class X-K as the control class. The results of data analysis showed that the N-Gain of the experimental class was 0.71 in the high interpretation while the N-Gain of the control class was 0.41 in the medium interpretation. Hypothesis testing shows the value of Asymp. Sig (2.tailed) value of <0.000 so it can be concluded that there are differences in student learning outcomes in economic subjects in the experimental class before, and after treatment.